KINERJA SISTEM AGRIBISNIS USAHA PENGGEMUKAN SAPI DI DESA ADIREJO KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH (STUDI KASUS DI PT INDO PRIMA BEEF) - Indah, Iva Mutiara; Lestari, Dyah Aring Hepiana; Sayekti, Wuryaningsih Dwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This study aims to analyze the performance of the agribusiness system of the beef cattle fattening business at PT Indo Prima Beef. The research method used is the case study method, located at PT Indo Prima Beef, Terbanggi Besar District of Central Lampung Regency. Data were collected in November-December 2022. Data were analyzed using qualitative and quantitative descriptive analysis. The results showed that the performance of the production facilities supply subsystem was good, as analyzed by the agribusiness index analysis and six right. However, there are still insufficiencies, such as locations close to settlements, feed is not in the right place, and labor is not in the right type, quality, and quantity. The performance of the cultivation subsystem is suitable for cultivation because it has an R/C ratio value of >1, but currently, the company has not conducted mating with artificial insemination. The performance of the marketing subsystem is good as analyzed by the agribusiness index and marketing mix analysis (4P). Beef cattle marketing channels are large traders (abattoirs), retailers, and consumers. The performance of the supporting service subsystem is good, the services utilized by PT Indo Prima Beef are financial institutions, research institutions, government policies, transportation facilities, communication and information technology facilities, and supply stores for production facilities. Overall, the performance of the agribusiness system at PT Indo Prima Beef has been running well with a weighted agribusiness index of 81.51%. Keywords: Agribusiness index, agribusiness system, beef cattle.